Quarter Century of Quality Management and Consumer Protection in Romania (Global Journal of Management and Business Research, 2015)
The former socialist/ communist rule kept Romania almost isolated from the Western World during about half a century (1945-1989). All about 7000 Romanian former state-owned companies (which were operational at the end of 1989) were obliged, by Law, starting the years '60, to organize their own so-called "CTC (Technical Quality Control) Department", in order to only inspect the quality of their products. In 1992, two years only after the fall of Ceausescu's dictatorship, in Romania were published both the first Romanian edition of famous ISO 9001 standard (in 1987, when ISO published its first international issue, the former Romanian regime did not allow the translating of it in Romanian!) and the first Consumer Protection Act in Romania's history.
Keywords: l romania; quality management; consumer protection; legislation; organizations; approaches